Chivalry's Double-edged Sword: How Girls' and Boys' Paternalistic Attitudes Relate to Their Possible Family and Work Selves. - Farkas, Timea; Leaper, Campbell (Sex Roles, 2016)
Paternalism refers to the ideology that women need men's protection (Glick and Fiske ), which is associated with greater acceptance of the gender status quo (Jost and Kay ) and lower feelings of agency and competence among women (Dumont et al. ). To consider the potential impact of paternalistic attitudes during adolescence, we investigated girls' and boys' paternalistic attitudes in relation to their possible family and career selves. The sample comprised 201 U.S. adolescents from California high schools ( M = 17.49 years; 46% girls) from ethnically diverse backgrounds (49% White, 26% Asian, 25% other). Participants completed survey measures of paternalistic attitudes, possible family and work selves, and other constructs. Possible work selves included occupations traditionally associated with men (computers, science, business/law, and action-oriented jobs [e.g., firefighter, mechanic]) or with women (elementary-school teacher and aesthetic-oriented jobs [e.g., fashion model, dancer]). There were significant average gender differences in paternalism (boys higher), future family hopes (girls higher), future careers associated with women (girls higher), and most future careers associated with men (boys higher); we found no significant gender difference in business/law career interest. Paternalistic attitudes significantly predicted several aspects of possible selves in hypothesized directions: future family hopes (positive association for girls and boys), future business/law and action-oriented careers (positive for boys), aesthetic-oriented careers (positive for girls), and science careers (negative for girls). Other hypothesized patterns were not indicated. Findings are interpreted as reflecting the potential influences of paternalistic attitudes in the formation of adolescents' possible family and work selves.